The characteristics of winter soft wheat collection samples according to their adaptive properties of the trait “mass fraction of protein in kernels” - N. S. Kravchenko; E. V. Ionova; S. V. Podgorny; N. N. Vozhzhova (Зерновое хозяйство России)
The current paper has presented the study results of winter soft wheat samples according to the adaptive properties of the trait “mass fraction of protein in kernels”. The purpose of the research was to identify the winter soft wheat genotypes with high productivity, mass fraction of protein and adaptive properties to growing conditions. The objects of research were winter soft wheat varieties of various ecological and geographical origin. The field trials were carried out in 2016–2018 on the fields of the department for winter wheat breeding and seed production of the FSBSI “Agricultural Research Center “Donskoy”. Protein percentage in kernels was determined by a “SpektraStar 2200” infrared analyzer. On average, over the years of research, the protein percentage in the grain ranged from 12.7% (“Webster”) to 14.8% (“L 19578”). It was determined that the sample “L 19578” (14.8%) belonged to the1st class, 22 wheat samples corresponded to the 2nd class and 8 samples corresponded to the 3rd class according to the “mass fraction of protein in kernels”. It was found that the weather conditions of the year had a decisive effect on protein formation (90.7%). The factor “variety” affects the manifestation of the trait by 6.4%. The interaction between the factors is significantly 2.9%. There have been identified the genotypes responsive to the improvement of growing conditions, in which bi is significantly more than 1, i. e. “Vinnichanka” (bi = 2.82), “Slavna” (bi = 1.88), “Zlatka” (bi = 1.87) and others. There have been identified the genotypes with negative bi values “Ermak” (bi = –0.70), “L 19578” (bi = –1.41), “No. 42 CIMMYT” (bi = –1.99) and others, which indicates their high adaptability to growing conditions. There has been determined a group of varieties for which the bi values did not significantly deviate from 1, they are “Shestopalivka” (bi = 0.54), “Chornyava” (bi = 0.73), “KS 96 WGRC 37” (bi = 1.38), etc. This shows that a change of the trait of these varieties will exactly follow a change in environmental conditions. There has been established that the most stable varieties of environmental conditions were the varieties “Ermak” (Cv = 1.1%; Hom = 11 637.6), “Shestopalivka” (Cv = 1.4%; Hom = 2580.2), “MV 15-09” (Cv = 1.7%; Hom = 1784.9) and others, as evidenced by the combination of the lowest values of the coefficient of variation and high homeostaticity. The calculation of the interaction showed a high correlation between Cv and S2i (r = 0.91), with bi (r = 0.55) and with Hom (r = –0.56), which significantly allows using Cv for preliminary estimation of varieties on homeostatic, ecological adaptability and stability.